Application of the Power Grid Business Carrying on Low Earth Orbit Broadband Satellite Internet - Liang ZHU; Shaobo QI; Bo YANG; Bingyu XU; Zifan LI; Shijie ZHANG (天地一体化信息网络)
LEO (Low-earth-orbit) broadband satellite internet can provide a lot of user with all-time network coverage, broadband access and information transport service, which has the advantage of high capacity, broad band, low delay and high elasticity as space information network.This made the application service in vertical industry based on LEO satellite network become research hotspots.Based on the research and analysis of power grid communication demand, the application solution of power industry based on LEO broadband satellite internet were proposed, focused on three core business of power grid, included the power grid construction, power grid operation, and emergency rescue.Also, the design of system composition, workflow, and satellite terminal architecture were researched.Further, the transmission performance, continuous communication, and service switching of mobile satellite terminal were tested based on LEO broadband satellite network, which could provided low delay and high capacity for remote data transmission.The result was consultant significance for future application development and engineering implementation in power industry.